ADVANCED SOLUTIONS IN THE TECHNOLOGY OF ANTIBACTERIAL CERAMIC TILES: Array - Savvova, O.; Pokroeva, Ya.; Voronov, G.; Kovalenko, S. (Municipal economy of cities. Series: «Economy science», 2022)
The growing demand for competitive high-quality ceramic tiles in the world is analyzed, due to the growth in the construction industry for 2021-2026, with the dominance of leading companies in the Asia-Pacific region. The main trends in the development of the ceramic tile market in Ukraine have been determined. The priority is given to the fragmentation of the global ceramic tile market due to technological progress and product innovations, which will allow domestic manufacturers to compete with well-known global brands. It was determined that an urgent global problem in the context of the spread of the COVID-19 pandemic is to ensure the quality of life of people and preserve a unique ecosystem by developing antibacterial materials that are non-toxic, durable and have a significant bactericidal effect. It has been found that the most well-known way to ensure the antibacterial effect of glass materials, is to use the properties of silver ions in their composition, is not effective, given its cost and toxicity. The aim of the work is to develop ecological bactericidal glass composite coatings on ceramics with prolonged action against a wide range of pathogenic microorganisms. To study the antibacterial properties of the sclopcoats, a culture of Escherichia Coli bacteria was selected. To determine the bactericidal effect of the glass coating, a method for assessing the toxicity of substances by the dehydrogenase activity of bacteria was chosen. The antibacterial glaze developed at private joint stock company "Kharkov Tile Plant" is characterized by a high ability to inhibit the enzymatic activity of pathogenic microorganisms and has a prolonged effect, which determines the effectiveness of its application in a pandemic. The implementation of the results of the work will allow solving an important socio-economic task of Ukraine in the direction of increasing the competitiveness of domestic ceramic tiles and implementing state policy to prevent a pandemic and overcome its consequences.